2011
DOI: 10.1111/j.1365-2125.2010.03894.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse relationship between leukaemic cell burden and plasma concentrations of daunorubicin in patients with acute myeloid leukaemia

Abstract: WHAT IS ALREADY KNOWN ABOUT THE SUBJECT• In vitro studies show that daunorubicin (DNR) cytotoxicity decreases with increasing cell density because of a high cellular uptake and depletion of drug in the medium.• It is not known whether such an effect also occurs in vivo. WHAT THIS STUDY ADDS• We have shown that a large leukaemic cell burden lowers the plasma concentration of DNR in patients with acute myeloid leukaemia.• Our analysis supports that a large leukaemic cell burden increases the central volume of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In a previous study, it was shown that the baseline white blood cell count (bWBC) was inversely correlated with the plasma concentration of Dnr [11]. Interestingly, a similar effect has been described for Ara-C in a constant infusion regimen [12], whereas other investigators did not find this correlation for patients receiving higher doses of Ara-C (1,000-3,000 mg/m 2 ) [13].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…In a previous study, it was shown that the baseline white blood cell count (bWBC) was inversely correlated with the plasma concentration of Dnr [11]. Interestingly, a similar effect has been described for Ara-C in a constant infusion regimen [12], whereas other investigators did not find this correlation for patients receiving higher doses of Ara-C (1,000-3,000 mg/m 2 ) [13].…”
Section: Introductionmentioning
confidence: 52%
“…The reduction in OFV indicated that there was also support for this relationship in the current data. For comparison, the differences in parameter estimates and uncertainties, along with the parameter estimates from the prior study [11], can be seen in Table 3. The Vc was increased by 1.9% for each increase in bWBC of 1 9 10 6 cells/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B). This is a clinically relevant drug resistance level as DNR dosing during induction regimens is in the range of 60 -80 mg/m 2 for adult (Ͼ15 years) ALL patients (23), corresponding to plasma DNR concentrations of ϳ0.2-1.4 M after a 1-h infusion (24). The generation and characteristics of the HL60/R10 cells are described in Ref.…”
Section: Cem/r2 Cells Are Resistant To Dnr and Overexpress P-gp-mentioning
confidence: 99%